2021
DOI: 10.1001/jamanetworkopen.2021.11806
|View full text |Cite
|
Sign up to set email alerts
|

Estimated Cardiorespiratory Hospitalizations Attributable to Influenza and Respiratory Syncytial Virus Among Long-term Care Facility Residents

Abstract: IMPORTANCE Older adults residing in long-term care facilities (LTCFs) are at a high risk of being infected with respiratory viruses, such as influenza and respiratory syncytial virus (RSV). Although these infections commonly have many cardiorespiratory sequelae, the national burden of influenzaand RSV-attributable cardiorespiratory events remains unknown for the multimorbid and vulnerable LTCF population.OBJECTIVE To estimate the incidence of cardiorespiratory hospitalizations that were attributable to influen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 53 publications
0
13
0
Order By: Relevance
“…Modelling studies have shown greater rates of hospitalization due to hRSV in adults with high-risk conditions [49,50]. In this context, Prasad et al [38] in New Zealand and Branche et al [39] in USA reported significantly higher hRSV hospitalization rates among adults with chronic diseases affecting the cardiovascular system, or chronic obstructive pulmonary disease, diabetes, or end-stage renal disease, as compared with adults of similar age without each corresponding condition.…”
Section: Discussionmentioning
confidence: 99%
“…Modelling studies have shown greater rates of hospitalization due to hRSV in adults with high-risk conditions [49,50]. In this context, Prasad et al [38] in New Zealand and Branche et al [39] in USA reported significantly higher hRSV hospitalization rates among adults with chronic diseases affecting the cardiovascular system, or chronic obstructive pulmonary disease, diabetes, or end-stage renal disease, as compared with adults of similar age without each corresponding condition.…”
Section: Discussionmentioning
confidence: 99%
“…Respiratory infections are a very frequent cause of morbidity and mortality in nursing homes whose etiological diagnosis has improved with the inclusion of new diagnostic technologies [74][75][76]. As for viral etiology, influenza, Respiratory Syncytial Virus (RSV) infection, Coronavirus and Metapneumovirus infections stand out [49,[77][78][79][80][81]. The most important bacterial pneumonia are pneumococcal pneumonia, [42,82,83] and polymicrobial aspiration pneumonia [84].…”
Section: What Measures To Reduce Respiratory Infection Have Been Show...mentioning
confidence: 99%
“…UTI is the most common bacterial infection among older people with disability (OPWD) and the third leading cause of infection‐related hospitalizations in older people, 8,9 which may further result in more serious illnesses and even death 10 . Although PI and UTI are preventive and treatable with medical treatment and appropriate care, many OPWD cannot afford long‐term care services and medical expenses, resulting in disease progression, complications, and related hospitalizations or even death 11,12 …”
Section: Introductionmentioning
confidence: 99%